2022
DOI: 10.1039/d1ya00057h
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic ethanolysis of high free fatty acid jatropha oil using Eversa Transform

Abstract: A reduction of the cost of enzymatic biodiesel is crucial to make it competitive with known technologies. A single-step process for the conversion of high free fatty acid oils into fatty acid ethyl esters using a low-cost lipase was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…However, increasing catalyst weight beyond the culmination point tends to decrease the ester conversion. This phenomenon may be explained by the tendency of enzyme lipase to form an aggregate due to a higher amount of the reactant . Furthermore, another reason is no significant volume of IPA is available in the reactant to fully suspend the enzyme lipase causing less mass transfer .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing catalyst weight beyond the culmination point tends to decrease the ester conversion. This phenomenon may be explained by the tendency of enzyme lipase to form an aggregate due to a higher amount of the reactant . Furthermore, another reason is no significant volume of IPA is available in the reactant to fully suspend the enzyme lipase causing less mass transfer .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be explained by the tendency of enzyme lipase to form an aggregate due to a higher amount of the reactant. 28 Furthermore, another reason is no significant volume of IPA is available in the reactant to fully suspend the enzyme lipase causing less mass transfer. 29 Other researchers suggested that this occurrence is due to the protein–protein interaction in the higher dosage of the enzyme.…”
Section: Resultsmentioning
confidence: 99%